The Problems assoicated with low frequencies in hearing aid amplification - A, Abdul Elah (Journal of All India Institute of Speech and Hearing, 1971)
Speech consists of frequencies ranging from about 100 Hz to 10 KHz. The range important for good understanding of speech extends from about 400 to 3000 Hz. (Silverman et al., 1960). In whispering, low frequencies are absent since the vibration of vocal cords does not occur. The absence of low frequencies makes the speech less audible. But in normal conversation vocal cords vibrate and consequently speech is carried to a greater distance. Further, experiments have shown that if high frequency components are suppressed, speech remains highly audible and ceases to be easily intelligible. From these findings it is evident that the low frequency components (mainly vowels) give power or energy to speech but intellgibility is provided by high frequency components (consonants). This differential functioning of high and low frequencies in the production and perception of speech has been a source of technical problem in the production and use of hearing aids.